(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is beetle of both reclamation sites and landfill space for the disposal of construction and demolition (CD) waste. It is important for India to adopt a strategy to reduce, reuse and recycle CD waste. One of the ways to achieve this is by The use of CD waste in paving blocks as partial replacement of fine aggregate, reducing the quantity of CD waste as well as the cost of fine aggregate in concrete. Different mix proportions were prepared for 0, 20, 40, 60, 80 replacement of CD wastes fine aggregate. The compressive strength of paving block was measured. The results showed that maximum strength is achieved between the ranges of 40 to 60 replacement of fine aggregate with CD waste fine aggregate, saving 3.28 cost of concrete. The study indicated that the CD waste can effectively replace fine aggregate with little increase in strength.